The Ecological Epistemology of Leuit in Sundanese Indigenous Communities: Local Wisdom in Environmental Law - Armansyah Armansyah; Ujang Badru Jaman (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2026)
The global ecological crisis requires environmental law that is not only technocratic but also contextual and participatory. This study reconstructs the Leuit ecological epistemology of the Sundanese indigenous community as a foundation for integrating local wisdom into Indonesian environmental law. In this study, which used a qualitative, critical ethnographic approach, data were collected through participatory observation, in-depth interviews, and legal–customary document analysis. Findings show that Leuit functions not merely as food storage but also as an ecological knowledge system that regulates spiritual, social, and environmental relations. Values such as murah-mawur, rewang, and customary prohibitions form a living legal system shaped by ritual and social consensus. As traditional leaders stated, "If the forest is destroyed, Leuit will be empty," while a full Leuit symbolizes preserved nature. The reconstruction highlights the integration of indigenous principles, empowerment of customary institutions, and ecologically grounded sanctions, proposing decolonization of environmental law to recognize local knowledge within national legal pluralism.